2020
DOI: 10.1002/sd.2049
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and corporate financial performance: A study based on the Brazilian Corporate Sustainability Index (ISE)

Abstract: There is a growing trend of seeking to move toward sustainable development and because of this, together with the increasingly watchful eye of society, companies are increasingly taking note of this new niche in the stock market. Thus, fund managers and investors see a need to align profits with environmental, social and economic variables in business management as well as corporate governance. The Brazilian Corporate Sustainability Index (Índice de Sustentabilidade Empresarial—ISE) was created in 2005 by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 96 publications
0
7
0
2
Order By: Relevance
“…Thus, this study contributes to sustainable development literature in the following way. While there is evidence that if companies better pursue sustainability development goals, it can increase their value in the future (de Castro Sobrosa Neto et al, 2020), there is no clear understanding of whether or how it actually affects company performance. Prior research has suggested that taking advantage of e-business today is increasingly demanding sustainability engagement (Aras & Crowther, 2009;Ol ah et al, 2019;Pålsson et al, 2017) (Autry & Golicic, 2010), but finding key suppliers and building close relationships with the aim of more competitive advantages in the marketplace is challenging (Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study contributes to sustainable development literature in the following way. While there is evidence that if companies better pursue sustainability development goals, it can increase their value in the future (de Castro Sobrosa Neto et al, 2020), there is no clear understanding of whether or how it actually affects company performance. Prior research has suggested that taking advantage of e-business today is increasingly demanding sustainability engagement (Aras & Crowther, 2009;Ol ah et al, 2019;Pålsson et al, 2017) (Autry & Golicic, 2010), but finding key suppliers and building close relationships with the aim of more competitive advantages in the marketplace is challenging (Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of e-business, it is often perceived that the traditional goal of firms, defined as providing profits for owners, has been complemented by more socially and environmentally sustainable goals (T. Oliveira & Martins, 2010;Ukko et al, 2019). Companies are paying more attention to the business perspective of corporate sustainability, as it is indicated that if companies better pursue sustainability development goals, it can increase their future value (de Castro Sobrosa Neto et al, 2020). While collaboration plays an important role in helping companies to become more sustainable (Govindan et al, 2016;Lozano et al, 2021;Seuring & Gold, 2013), firms must focus on managing both internal and external relations to become more socially and environmentally responsible while retaining economic sustainability (Luzzini et al, 2015;Shang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing degradation of the natural environment, an increasing number of organizations are examining how corporations can contribute to sustainability through biodiversity conservation initiatives (Adler et al, 2018; de Castro Sobrosa Neto et al, 2020). For this reason, corporations are adopting a broader range of biodiversity management approaches into their formal business strategies, namely biodiversity certification schemes, biodiversity reporting, stakeholder engagement, and biodiversity offset programs (Boiral, 2016; Boiral & Heras‐Saizarbitoria, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given the growing awareness among Chinese MNCs regarding the importance of CSR initiatives in Africa, exploring how Chinese MNCs in Africa can achieve desirable corporate performance through CSR engagement is critical to promote mutual benefits for both Chinese MNCs and African societies. Since existing literature reveals inconclusive results in respect of the relationship between CSR engagement and corporate performance of MNCs' subsidiaries (Dai et al, 2018; de Castro Sobrosa Neto et al, 2020; do Prado et al, 2020; Luo et al, 2017), it is suggested that mainstream literature may have overlooked certain mediating and moderating factors that may significantly impact this relationship (Aguilera‐Caracuel et al, 2017; Ali et al, 2020). Considering the context and conditions outlined above, we aimed to examine the direct relationship between CSR engagement and corporate performance for Chinese MNCs operating in Africa and, furthermore, to explore this particular relationship with emphasis on moral legitimacy as a mediating factor and institutional distance as a moderating factor.…”
Section: Introductionmentioning
confidence: 99%